2021
DOI: 10.1155/2021/8793187
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Prognostic Factors and Treatment Modes of Patients with Recurrent Endometrial Carcinoma

Abstract: Objective. Recurrence of endometrial cancer after initial treatment can be complex and difficult to treat. The current main treatment modalities for patients with recurrent endometrial cancer (REC) include chemotherapy, radiotherapy, and surgery, which vary according to the individual patient. However, REC is often associated with a poor prognosis, and it is therefore important to investigate the risk factors affecting REC prognosis and to explore appropriate treatment modalities to improve the prognosis and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…There are still limits of this study: (1) We identified the downregulation of ATM in ECs, but the factors that contribute to ATM downregulation remain unclear. ATM expressions are regulated by various factors at both transcriptional and post-transcriptional levels.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…There are still limits of this study: (1) We identified the downregulation of ATM in ECs, but the factors that contribute to ATM downregulation remain unclear. ATM expressions are regulated by various factors at both transcriptional and post-transcriptional levels.…”
Section: Discussionmentioning
confidence: 93%
“…Endometrial cancer (EC) is a type of epithelial malignant tumors occurring in the endometrium. 1 It is one of the most prevalent gynecologic cancers, which poses a serious threat to women’s health and lines the fourth after mammary glands cancer, lung cancer and rectum cancer. 2 , 3 EC can be classified basically into two types based on Bokhman’s classification complemented with detailed genetic, biochemical and histopathological studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%